CONVERSATIONAL IMPLICATURE AS FOUND IN BUYERS’ AND SELLERS’ INTERACTION IN THE TRADITIONAL MARKET OF LUBUK ALUNG - Indah Nadya Irnanda; Hamzah Hamzah (Universitas Negeri Padang, 2017)
The purpose of this study was to analyze the conversational implied meaning or called implicature in conversation between buyers and sellers in the traditional market of Lubuk Alung based on Grice‟s Cooperative Principle and its maxims. The main objective of this study was to analyza how utterance can go beyond its literal meaning by flouting some maxims by the speakers since flouting of maxims can generate implicature. Moreover, this study also analyzed the comparisons between male and female in flouting of maxim in buyers’ and sellers’ interaction in traditional market. The type of this research was descriptive qualitative by explaining conversational implicature without statistical procedure and counting process. Data from this study were obtained from conversations between buyers and sellers in traditional market that have been recorded by the researcher. After analyzing the data, researcher found the speakers (sellers and buyers) were more often flouted the maxim of manner. In contrast, maxim of quality was the fewest to be flouted by the speakers. In the conversation that have been recorded, female are more often flouted the maxim than male because female were more likely to bargain in the traditional market than male.